Application of New Approach of design flow for Hardware/Software Embedded System with the Use of Design Patterns in Fuzzy control system - Ali Bouyahya; Yassine Manai; Joseph Haggège (Institute of Advanced Engineering and Science, 2015)
This paper present a new method of conception of hardware/software embedded system design methodology based on use of design pattern approach called Abstract_factory. We called this new design tool “smart cell”. The main idea of the conception of embedded systems design is based on the used of object-oriented design ULM2.0. When the smart-cell is implemented, we justify their uses as a design tool that allows, first, to develop a specified application of fuzzy controller called PDC (parallel distributed conpensation). Second, the specification of the generation phases of the system architecture design, and eventually partitioning the application on heterogeneous platform based on hardware resource DSP and FPGA software to illustrate the proposed approach.